Biological macromolecule chitosan grafted co-polymeric composite: bio-adsorption probe on cationic dyes - Khairkar, Shyam R.; Pansare, V. Shubham; Shedge, Amol A.; Chhatre, Shraddha; Kulal, Dnyaneshwar K.; Patil, Vishwanath R.; Pansare, V. Amol (Polymer Bulletin, 2022)
Chitosan biological macromolecule is a versatile polymer; chemical modification has been carried out that lead to the formation of chitosan grafted polymers composites (Chito-g-PC). We proposed synthesis of six various Chito-g-PC as sorbents for toxic dyes. A novel graft copolymerization method based on radical polymerization with vinyl monomer like acrylic acid, acrylamide, N-isopropylacrylamide, methacrylic acid and polyacrylonitrile were utilized in order to address the large amount of swelling at four different pH buffers solution. The effect of initiator and monomer concentration, time and temperature on % grafting and % grafting efficiency were performed. Comparative characterization of Chito and Chito-g-PC were evaluated by SEM, XRD and FTIR, as well as solubility characteristics of the composites were determined by various pH buffer solution. Cationic toxic dyes Malachite green (MG) and Methylene blue (MB) were selected as the sorbet, and Chito-g-PC were used as biosorbents. Thermodynamic analysis showed that the sorption process was spontaneous and endothermic with an increased randomness. The sorption experiments were realized with six different Chito-g-PC for MG and MB at various pH.
Keywords: Acrylamide; acrylic acid; Bio sorbent; Chitosan biological macromolecule

Deciphering the sensing of alpha-amyrin acetate with hs-DNA: a multipronged biological probe - Pansare, V. Amol; Shedge, Amol A.; Sonawale, Maryappa C.; Pansare, V. Shubham; Mahakal, Akshay D.; Khairkar, Shyam R.; Chhatre, Shraddha Y.; Kulal, Dnyaneshwar K.; Patil, Vishwanath R. (RSC Advances, 2022)
In this study, we focus on the biomimetic development of small molecules and their biological sensing with DNA. The binding of herring sperm deoxyribonucleic acid (hs-DNA) with naturally occurring bioactive small molecule alpha-amyrin acetate (alpha-AA), a biomimetic - isolated from the leaves of Ficus (F.) arnottiana is investigated. Collective information from various imaging, spectroscopic and biophysical experiments provides evidence that alpha-AA is a minor groove sensor of hs-DNA and preferentially binds to the A-T-rich regions. Interactions of different concentrations of small molecule alpha-AA with hsDNA were evaluated via various analytical techniques such as UV-Vis, circular dichroism (CD) and fluorescence emission spectroscopy. Fluorescence emission spectroscopy results suggest that alpha-AA decreases the emission level of hsDNA. DNA minor groove sensor Hoechst 33258 and intercalative sensor EB, melting transition analysis (T-M) and viscosity analysis clarified that alpha-AA binds to hs-DNA via a groove site. Biophysical chemistry and molecular docking studies show that hydrophobic interactions play a major role in this binding. The present research deals with a natural product biosynthesis-linked chemical-biology interface sensor as a biological probe for alpha-AA: hs-DNA.